The Institution of Legal Liability in the Digital Age: International Legal Standards, Administrative, Financial and Criminal Aspects - Volkova, Yuliia; Leheza, Yuliia; Pavlov, Volodymyr; Goncharenko, Ganna; Blahodarnyi, Andrii (Jurnal Cita Hukum, 2025)
The article reveals the issue of legal responsibility within the context of digitalization in society. It is indicated that legal obligation, as a tool for coercion and the restoration of law and order, has always depended on the form of social relations. Today, digitalization has given rise not only to new objects of legal protection (personal data, digital assets, information security), but also to new subjects, such as platforms, algorithms, and autonomous systems. It is stated that the formation of the digital state leads to the transformation of traditional forms of public law responsibility, primarily administrative. In the digital age, not only is the form of offenses changing, but also how they are committed, recorded, detected, and proven. Administrative liability is becoming a tool for rapid response to mass violations in the fields of e-governance, personal data processing, cybersecurity, digital platform use, artificial intelligence, and telecommunication services. It is concluded that, accordingly, the institution of legal responsibility in the digital age is a system of prevention, regulation, self-control, and international cooperation. It must be adaptive, technologically literate, and human rights. The quality of legal mechanisms in the digital sphere determines whether the rule of law will remain effective in the context of digital transformation. REFERENCES: A Digital Agenda for Europe: Communication from the Commission to the European Parliament, the Council, the European Economic and Social Committee and the Committee of the Regions – Brussels, 19.5.2010, COM (2010) 245 final. http://eurlex.europa.eu/legalcontent/EN/TXT/PDF/?uri=CELEX:52010DC0245R (01)&from=EN Additional Protocol to the Convention on Cybercrime on the criminalization of acts of a racist and xenophobic nature committed through computer systems: Council of Europe; Protocol, International Document of 28.01.2003 https://zakon.rada.gov.ua/laws/show/994_687#Text Association Agreement between Ukraine, of the one part, and the European Union, the European Atomic Energy Community and their Member States, of the other part: International document of 27.06.2014. http://zakon3.rada.gov.ua/laws/show/984_011 Bukht, R., Heeks, R.: Digital Economy Policy in Developing Countries, 2018. https://diode.network/publications/ Bundesrecht konsolidiert: Gesamte Rechtsvorschrift für Signaturgesetz. https://www.ris.bka.gv.at/GeltendeFassung.wxe?Abfrage=Bundesnormen&Gesetzesnummer=10003685&FassungVom=2016-06-30&ShowPrintPreview=True Convention on Cybercrime Council of Europe; Convention, International Document of 23.11.2001 https://zakon.rada.gov.ua/laws/show/994_575#Text Demchyshak, N., Hlutkovskyi, M. Rozvytok tsyfrovoi ekonomiky v Ukraini: kontseptualni osnovy, priorytety ta rol innovatsii. Innovatsiyna ekonomika, 2020? 5-6, 43-48. Digital lawyers. IT in Law: Blockchain, Online Services, Chatbots, and Legal Tech Startups. https://osvita.diia.gov.ua/courses/digital-lawyers Digitalisation: Administration. https://www.bundeskanzleramt.gv.at/en/agenda/digitalisation/administration.html Drozd O., Dorokhina Yu., Leheza Yu., Smokovych M., Zadyraka N. Cassation filters in administrative judicial procedure: a step in a chasm or a novel that Ukrainian society expected? Amazonia investiga. Volume 10 - Issue 40: 222-232 / April, 2021 E-Government und E-Commerce sind im Vormarsch in Belgien. https://statbel.fgov.be/de/nachrichten/e-government-und-e-commerce-sind-im-vormarsch-belgien E-Government-Gesetz. https://www.parlament.gv.at/gegenstand/XXVII/I/1443 European Experience of Normative and Project Support for the Development of the Information Society: Conclusions for Ukraine: Analytical Report. National Institute for Strategic Studies. Kyiv, 2014. 76 p. European Experience of Normative and Project Support for the Development of the Information Society: Conclusions for Ukraine: Analytical Report. National Institute for Strategic Studies. Kyiv, 2014. 76 p. Horbalinskiy V., Markova O., Volkovа Yu., Litoshko V., Hlukhoveria K. Modalities of protection of the rights of individuals according to the administrative-procedural order and in legal-administrative procedures Cuestiones Políticas, 41(78), р. 94–103. https://doi.org/10.46398/cuestpol.4178.06 Kobrusieva, Yevheniiа. Leheza, Yevhen. Rudoi, Kateryna. Shamara, Oleksandr. Chalavan, Viktor. 2021. International standards of social protection of internally displaced persons: administrative and criminal aspects. Jurnal cita hukum indonesian law journal. Vol 9, No 3, 461–484. DOI: https://doi.org/10.15408/jch.v9i3.23752 Kulinich, Olha. Leheza, Yevhen. Zadyraka, Nataliia. Taranenko, Kseniia, Kostiuk, Tetiana. 2023. Electronic Judicial Procedure as an Element of Access to Justice Regarding Protection of Rights of Individuals: Legal, Administrative, Theoretical, and Informational Aspects. Jurnal cita hukum indonesian law journal. 11 (3), 443–456. DOI: https://doi.org/10.15408/jch.v11i3.36298 Kumeiko Andrii, Artur Gordienko, Yulia Volkova, Ganna Goncharenko, Andrii Blahodarnyi State Safety as an Object of Legal Protection in Ukraine Studies in Science of Science | ISSN: 1003-2053 https://sciencejournal.re/ | Volume 42, Issue 11, 2024 https://doi.org/10.5281/zenodo.14242254 Leheza, Y., Kolomoiets, Y., Chalyk, V., Kovalchuk, Y., & Sakhno, A. (2024). Foreign experience of financial-legal and administrative-legal regulation of the activities of public administration bodies. Revista do Curso de Direito do UNIFOR, 15(1), 51–60. DOI: https://doi.org/10.24862/rcdu.v15i1.1832 Leheza, Y., Korniienko, M., Berezniak, V., Мariienko, А., & Radchuk, A. (2024). Legal Regulation of Liability for Illegal Deportation of Children: Administrative, Criminal Aspects, Experience of Ukraine and International Standards. Revista Jurídica Portucalense, 257–274. https://doi.org/10.34625/issn.2183-2705(36)2024.ic-11 Leheza, Y., Shcherbyna, Bogdan. Leheza, Yulia. Pushkina, Olena & Marchenko O. (2023). “Features of Applying the Right to Suspension or Complete/ Partial Refusal to Fulfill a Duty in Case of Non-Fulfilment of the Counter Duty by the Other Party According to the Civil Legislation of Ukraine.” Revista Jurídica Portucalense, 340–359. Retrieved from https://revistas.rcaap.pt/juridica/article/view/29662 Leheza, Yevhen. Filipenko, Tatiana. Sokolenko, Olha. Darahan, Valerii, Kucherenko, Oleksii. 2020. Ensuring human rights in Ukraine: problematic issues and ways to address them in the social and legal sphere. Cuestiones políticas. Vol. 37 №º 64 (enero-junio 2020). P. 123–136. DOI: https://doi.org/10.46398/cuestpol.3764.10 Leheza, Yevhen. Pisotska, Karina. Dubenko, Oleksandr. Dakhno, Oleksandr. Sotskyi, Artur. “The essence of the principles of Ukrainian law in modern jurisprudence”. Revista jurídica portucalense, December (2022): 342-363. https://doi.org/10.34625/issn.2183-2705(32)2022.ic-15. Leheza, Yevhen. Shcherbyna, Bogdan. Leheza, Yulia. Pushkina, Olena. Marchenko, Olesia. (2024). Características de la suspensión o denegación total/parcial del cumplimiento de una obligación en caso de incumplimiento de la contraparte según la legislación civil de Ucrania. Novum Jus, 18(2), 131–150. https://doi.org/10.14718/NovumJus.2024.18.2.5 Leheza, Yevhen. Yerofieienko, Larysa. Komashko, Volodymyr. (2023). Propiedad intelectual en Ucrania bajo la ley marcial: regulación jurídica, aspectos administrativos y civiles. DIXI, 26(1), 1-11. https://doi.org/10.16925/2357-5891.2024.01.09 URL. https://revistas.ucc.edu.co/index.php/di/article/view/4960 Leheza, Yevhen. Yurovskа, Viktoriia. Zamryha, Artur. Ulozhenko, Vadym, Bohdan. Bohdana. (2024). Administrative and legal regulation of the status of internally displaced persons in Ukraine during the war. University of Western Australia Law Review. 51 (2). 297-313. https://www.uwa.edu.au/schools/-/media/documents/uwa-law-review/volume-51-issue-2/leheza-et-al-formatted.pdf Markets in Crypto-Assets Regulation (MiCA). https://www.esma.europa.eu/esmas-activities/digital-finance-and-innovat Matveenko I.V. Role of Information and Communication Influences in the Process of Implementation of Electronic Governance in Foreign Countries: Experience for Ukraine. Public governance. 2016. № 1. p. 135-145. Matviichuk, Anatolii. Shcherbak, Viktor. Sirko, Viktoria. Malieieva, Hanna. Leheza, Yevhen. 2022. Human principles of law as a universal normative framework: Principios humanos del derecho como marco normativo universal. Cuestiones Políticas, 40(75), 221–231. https://doi.org/10.46398/cuestpol.4075.14 Nalyvaiko, Larysa Leheza, Yevhen, Sachko, Oleksandr. Shcherbyna, Victor. Chepik-Trehubenko. Olha. 2022. Principles of law: Methodological approaches to understanding in the context of modern globalization transformations. Ius Humani. Law Journal, 11(2), 55–79. https://doi.org/https://doi.org/10.31207/ih.v11i2.312 OECD Digital Economy Outlook 2017, OECD Publishing, Paris. http://dx.doi.org/10.1787/9789264276284-en On approval of the Concept of development of electronic governance in Ukraine: Order of the Cabinet of Ministers of Ukraine dated 20.09.2017 No. 649-r. http://zakon3.rada.gov.ua/laws/show/649-2017-%D1%80 On approval of the Concept of the State Target Program for the Creation and Functioning of the Information System for the Provision of Administrative Services for the Period up to 2017: Order of the Cabinet of Ministers of Ukraine dated 24.07.2013 No. 614-r. URL: http://zakon3.rada.gov.ua/laws/show/614-2013-r On the National Program of Informatization: Law of Ukraine of February 4, 1998, No. 74/98-VR. URL: https://zakon.rada.gov.ua/laws/show/74/98-vr/print (expired). Ostapchuk, O., Baksalova O., Babiy, I. Sut ta tendentsii zminy finansovoho menedzhmentu v umovakh posylenoi tsyfrovizatsii ekonomiky. Modeling the development of the economic systems. 2022 (2), 167-172. Pashchak M.Z., Plotnikova O.V. Directions of Implementation of the Experience of Development of E-Governance in Chile and Belgium in Ukraine. Shelfmark: "Future UA". 2017. https://knute.edu.ua/file/NjY4NQ==/099bcfe3ac1a6b325d46cb4e0c6b1469.pdf Pizhuk, O.I. Tsyfrova transformatsiia ekonomiky Ukrainy: obmezhennia ta mozhlyvosti. Irpin, Universytet DFS Ukrainy. 2020 Rabinovych P. M. Fundamentals of the General Theory of Law and the State. Manual. View. 10th, add. Lviv: Krai, 2008. 224 p. Semenoh, A.Yu. Tsyfrovi finansovi posluhy yak osnovnyi produkt diialnosti fintekh-kompanii. Visnyk SumDU, Ser. «Ekonomika», 2021 (4), 142-152. Sinkevych, O., YurovskаV., Komissarova, N., Tkachenko, O., & Leheza, Y. (2024). Subjects of public authority in matters of combating terrorism: legal regulation, administrative, and criminal aspects. Ius Humani. Law Journal, 13(1), 1–14. https://doi.org/10.31207/ih.v13i1.332 Stepanov V.Y. Problems and Prospects of the Information Society. State building. 2012. № 2. http://nbuv.gov.ua/UJRN/DeBu_2012_2_4 Strategy for the Development of the Information Society in Ukraine: Decree of the Cabinet of Ministers of Ukraine of May 15, 2013 No. 386-r. Official Gazette of Ukraine. 2013. № 44. Century. 1581 Syvolapenko T.L. Experience of foreign countries in the implementation of digital concepts: realities and prospects for Ukraine. State and regions. Series: Public Administration, 2019. № 3 (67). pp. 108-112 Tylchyk, Vyacheslav. Matselyk, Tetiana. Hryshchuk, Viktor. Lomakina, Olena. Sydor, Markiian. Leheza, Yevhen. 2022. Administrative and legal regulation of public financial activity: Regulación administrativa y legal de la actividad financiera pública. Cuestiones Políticas, 40(72), 573–581. https://doi.org/10.46398/cuestpol.4072.33 UK's Digital Strategy. https://www.gov.uk/government/publications/uks-digital-strategy Verwaltungsverfahrensgesetz. https://www.bmi.bund.de/DE/themen/moderne-verwaltung/verwaltungsrecht/verwaltungsverfahrensgesetz/verwaltungsverfahrensgesetz-node.html Villasmil Espinoza, Jorge; Leheza, Yevhen; Holovii, Liudmyla. 2022. Reflections for the interdisciplinary study of the Russian Federation’s invasion of Ukraine in 2022: Reflexiones para el estudio interdisciplinario de la invasión de Ucrania por parte de la Federación Rusa en 2022. Cuestiones Políticas, 40(73), 16-24. https://doi.org/10.46398/cuestpol.4073.00 Voitko A. E-Government in Great Britain. Implementation and Problems. Actual Problems of Social and Political Sciences: Collection of Materials of the Scientific Conference / edited by O.I. Yaremenko, S.A. Lapshin. Vinnytsia, 2018. p. 236–239. Volkova Yu. Digitalisation of administrative procedures in the field of urban planning as a tool for combating corruption. Legal Scientific Electronic Journal. 2024. NO. 12, PP. 547-550 DOI https://doi.org/10.32782/2524-0374/2024-12/127 Volkova Yu. Digitalisation of the healthcare sector is a separate factor in preventing corruption. Digital Trends and Anti-Corruption Reforms in Public Administration: Scientific monograph. Riga, Latvia: Baltija Publishing, 2023. 228 p. DOI https://doi.org/10.30525/978-9934-26-369-9-20 Volkova Yu. Financial market in the digital era: processes of development and improvement Private and Public Law № 4/2024 DOI https://doi.org/10.32782/2663-5666.2024.4.5 http://www.pp-law.in.ua/index.php/4-2024 Volkova Yu. The impact of digitalization on the development of public administration services and the improvement of procedures for judicial consideration of administrative cases - Government in the European Union 2022. 291-310 DOI: https://doi.org/10.12797/9788381388894.16 Volkova Yu. The right to be forgotten as one of the fundamental human rights in the digital age Law and Society № 5/2024 DOI https://doi.org/10.32842/2078-3736/2024.5.16 Volkova Yu., Bon B., Borysenkо A., Leheza Yu., Leheza Y. Crypto Market Experience: Navigating Regulatory Challenges in Modern Conditions DOI: https://doi.org/10.30631/alrisalah.v24i2.1625 Forum Kajian Hukum dan Sosial Kemasyarakatan Vol. 24 No. 2, December 2024. 178-194 Zadyraka, Nataliia. Leheza, Yevhen. Bykovskyi, Mykola. Zheliezniak, Yevhenii. Leheza, Yulia. 2023. Correlation of Legal Concepts of Administrative Procedure and Administrative Liability in the Sphere of Urban Planning. Journal Cita Hukum Indonesian Law Journal. Vol. 11 No. 1, pp. 33-44, DOI: https://doi.org/10.15408/jch.v11i1.31784 Zaporozhchenko Yu., Leheza Yu., Volkova Yu., Pushkina O., Koval M. Human Rights and Features of their Protection in Conditions of War: International Legal Standards, Administrative, Constitutional and Criminal Aspects. Khazanah Hukum. 2023. Vol . 5, №3. P. 245-252.